Development of a smart domestic product - Tan, Wan Chin. (2008)
This dissertation looked into the development of smart domestic products. The vision of automated housemaids was introduced. After reviewing through the literatures, it was found that the vision was not far from reality. The commercial potentials and social benefits were the main motivation factors for this dissertation to pursue development.